A review on polyamine analogues and its cytotoxic effects against selected human cancer cell lines - Sahabudin, Adzly Hairee; Abdul Ghani, Radiah; How, Fiona Ni Foong; Halim, Norsuhana; Jamil, Masnizahani (2017)
Researches in compound containing sulphur and the polyamine transport system is beneficial in oncology as both affect cancer cells. Compounds containing sulphur such as organosulphur are known for its anti-cancer properties. Through various experiments by researcher, several new compounds were successfully synthesized to combat cancer cells. Some of the compounds that were successfully synthesized were the polyamine-sulphur compounds. By adding sulphur to known natural polyamine, the analogues will be delivered specifically to cancer cells via polyamine transport system (PTS). For the synthesis of the compound, carbon disulphide and benzyl chloride were added to the polyamine (Putrescine or Spermidine) via a method called Room Temperature Mediated Synthesis. The addition of carbon disulphide was to add the sulphur element while the addition of benzyl chloride was to make the compound bulkier and stable. For the addition of carbon disulphide only, the compounds were named PSA-1 and SSA-1 for putrescine and spermidine respectively while for the addition of both carbon disulphide and benzyl chloride were named PSA-2 and SSA-2. The compounds were then analyzed by using Fourier Transformed Infrared Spectroscopy (FTIR) and Gas Chromatography-Mass Spectroscopy (GC-MS) to determine the successful addition of sulphur and benzyl compound. The compounds were then tested with human lung adenocarcinoma cells (A549), human breast adenocarcinoma cell (MCF-7) and human colorectal adenocarcinoma cells (HCT-8). The cytotoxicity effects of these compounds were carried by using MTT assay against these in-vitro cells. The results show the cytotoxic effects were not potent against these cell lines as a higher concentration of compounds were needed to inhibit the cells growth.